Cysteine proteinase inhibitors regulate human and mouse osteoclastogenesis by interfering with RANK signaling - Stral̊berg, Fredrik; Henning, Petra; Gjertsson, Inger; Kindlund, Bert; Souza, Pedro P. C. [UNESP]; Persson, Emma; Abrahamson, Magnus; Kasprzykowski, Franciszek; Grubb, Anders; Lerner, Ulf H. (Wiley, 2013)
The cysteine proteinase inhibitor cystatin C inhibited RANKL-stimulated osteoclast formation in mouse bone marrow macrophage cultures, an effect associated with decreased mRNA expression of Acp5, Calcr, Ctsk, Mmp9, Itgb3, and Atp6i, without effect on proliferation or apoptosis. The effects were concentration dependent with half-maximal inhibition at 0.3 μM. Cystatin C also inhibited osteoclast formation when RANKL-stimulated osteoclasts were cultured on bone, leading to decreased formation of resorption pits. RANKL-stimulated cells retained characteristics of phagocytotic macrophages when cotreated with cystatin C. Three other cysteine proteinase inhibitors, cystatin D, Z-RLVG-CHN2 (IC50 0.1 μM), and E-64 (IC 50 3 μM), also inhibited osteoclast formation in RANKL-stimulated macrophages. In addition, cystatin C, Z-RLVG-CHN2, and E-64 inhibited osteoclastic differentiation of RANKL-stimulated CD14+ human monocytes. The effect by cystatin C on differentiation of bone marrow macrophages was exerted at an early stage after RANKL stimulation and was associated with early (4 h) inhibition of c-Fos expression and decreased protein and nuclear translocation of c-Fos. Subsequently, p52, p65, IκBα, and Nfatc1 mRNA were decreased. Cystatin C was internalized in osteoclast progenitors, a process requiring RANKL stimulation. These data show that cystatin C inhibits osteoclast differentiation and formation by interfering intracellularly with signaling pathways downstream RANK. © FASEB.
Keywords: c-Fos; Cystatin C; Nfatc1; Osteoclasts; CD14 antigen; cystatin C; cystatin d; cysteine proteinase inhibitor; I kappa B kinase alpha; messenger RNA; osteoclast differentiation factor; protein c fos; synaptotagmin I; transcription factor NFAT; transcription factor NFATc1; unclassified drug; animal cell; apoptosis; bone marrow cell; cell culture; cell differentiation; cell proliferation; controlled study; gene expression; macrophage; molecular mechanics; monocyte; nonhuman; osteoclastogenesis; osteolysis; phagocytosis; priority journal; protein expression; signal transduction; osteoclasts; Animals; Antigens, CD14; Blotting, Western; Bone Marrow Cells; Cell Differentiation; Cells, Cultured; Cysteine Proteinase Inhibitors; Gene Expression; Humans; Macrophages; Mice; Mice, Inbred C57BL; Monocytes; NFATC Transcription Factors; Proto-Oncogene Proteins c-fos; RANK Ligand; Receptor Activator of Nuclear Factor-kappa B; Reverse Transcriptase Polymerase Chain Reaction; Signal Transduction